Eurekan faults on northern Ellesmere Island, Arctic Canada: from Cenozoic strike-slip tectonics to recent seismicity - Brandes, Christian; Piepjohn, Karsten (Amsterdam [u.a.] : Elsevier Science, 2021)
The Eurekan deformation is a partially contractional Cenozoic tectonic event that affected large parts of the Arctic region. In the study area on northern Ellesmere Island, major NE-SW trending strike-slip faults occur, which are related to the Eurekan deformation. The outcrop data show that left-lateral strike-slip kinematics slightly dominate, but also right-lateral kinematics were documented. Cross-cutting relationships of the individual faults give evidence for multiple fault reactivations within major strike-slip zones. The reconstructed paleostress fields show two phases. The first phase started with a N-S compression and shifted over a NNE-SSW compression into a NNW-SSE compression. The second phase was a WNW-ESE compression. The paleostress field evolution reflects the movements of Greenland. During the Eurekan phase 1, Greenland moved northward and during Eurekan phase 2 it moved to the WNW. These motions likely controlled the stress field on northern Ellesmere Island. From the paleostress field analyses and the orientation of the strike-slip faults in the study area, it can be derived that the Eurekan phase 1 deformation is characterized by left-lateral strike-slip faults, whereas most-likely during Eurekan phase 2 the majority of right-lateral strike-slip faults formed. The paleostress field analysis implies that many Eurekan faults are reactivated Ellesmerian faults. Recent seismic events indicate ongoing tectonic activity at some of the major strike-slip faults. This sheds new light on the geodynamics of northern Ellesmere Island, which was mechanically coupled to the Greenland plate, and implies that under the recent stress field, earthquakes at strike-slip faults are still possible and some of these faults were active in at least three phases over the last 350 Myr.